Phosphor thermometry in heat transfer fluids and liquid organic hydrogen carrier systems using (Sr,Ca)SiAlN3:Eu2+ - Bollmann, Jonas; Hickl, Franziska; Preuster, Patrick; Zigan, Lars; Wasserscheid, Peter; Will, Stefan (Measurement Science & Technology, 2023)
Temperature control in heat exchangers in reacting and non-reacting flows is of great importance for process optimization. In this context, phosphor thermometry is a promising technique for remote planar temperature sensing. The thermometry technique is based on exciting a luminescent material by a laser pulse and analyzing the subsequent phosphorescence signal. A particular interesting application is chemical hydrogen storage using liquid organic hydrogen carrier (LOHC) systems. The knowledge of temperature fields is of special interest for the characterization and understanding of hydrogen release from the carrier liquid. We investigated the luminescence properties of the thermographic phosphor (Sr,Ca)SiAIN(3):Eu2+ ('SCASN:Eu2+') dispersed in different heat transfer fluids, in particular LOHC systems, using a newly developed calibration cell. As heat transfer fluids may be excited to fluorescence by the laser as well, their absorption and florescence behavior is studied to develop an excitation and detection concept for thermometry. We found strong absorption of the heat transfer fluids from the UV range to a wavelength of about 400 nm. In addition, fluorescence signals were found in the visible wavelength range, which can interfere with the phosphor emissions. These fluorescence signals should therefore be circumvented by utilizing the different luminescence decay times in the chosen detection strategy. For thermometry, the SCASN:Eu2+ particles were excited by a laser sheet of a 532 nm Nd:YAG laser. A spectrometer and photomultiplier tube (PMT) were used to detect the emission spectrum and phosphorescence decay time (PDT). Two temperature evaluation strategies were applied, which are based on either the intensity ratio of two spectral emission regions (two-color laser-induced phosphorescence) or the PDT. The results obtained show an applicable measurement range between 293 K and 598 K for the intensity ratio method with a maximum relative sensitivity of 0.12% K-1 at 293 K. For the PDT method, the phosphor allows measurements between 423 K and 598 K with a maximum relative sensitivity of 0.56% K-1 at 598 K.
CRIS-Team WoS Importer:2023-02-10
Keywords: heat transfer fluids; liquid phase; calibration cell; fluorescence; optical sensor; thermographic phosphors